KERJA SAMA BADAN KEAMANAN LAUT REPUBLIK INDONESIA DAN AUSTRALIAN BORDER FORCE DI BIDANG KEAMANAN MARITIM SEKTOR CAPACITY BUILDING PADA KEJAHATAN ILLEGAL FISHING DAN ILLEGAL MIGRANT PERIODE 2017-2021 - Khoirunnaja Saefudin (2023)
This study tries to outline the urgency of transnational crime problems such as Illegal Fishing and Illegal Immigrant, which occur every year and the ways are increasingly diverse. Transnational crimes are crimes that are committed at the borders of two or more countries in order to gain large profits so that they are considered a serious threat to the security and prosperity of a country. Maritime terrorism, narcotics, Piracy and armed robbery, Illicit trafficking in arms and weapons of mass destruction, Smuggling and trafficking of persons by sea, IUU Fishing, and Intentional damage to the marine environment are part of transnational crimes. So that in this era of globalization, the development of transnational crime is increasing. In the context of eradicating transnational crime especially from IUU Fishing and Illegal Migrant, the Republic of Indonesia Maritime Security Agency (Bakamla RI) and the Australian Border Force (ABF) cooperate in the maritime security sector in the capacity building sector for the 2017-2021 period. This study aims to describe the process of what the collaboration between Bakamla RI and ABF. This study uses qualitative approach and descriptive type of research that uses 2 data sources, namely primary and secondary. In analyzing this research, the author uses maritime security concept, security cooperation concept, collective security concept, and capacity building concept. The results of this research argument found that the collaboration between Bakamla RI and ABF was succesfull based on Axelrod & Keohane argument, this collaboration created capacity building that was created between them, including Capacity Building Exercises between Civilian Maritime Enforcement Agencies and Navy, Including Port Visits, ABF- Bakamla Senior Official Meeting (SOM), and Joint Capacity Building Exercise. Keywords: Cooperation, The Maritime Security Agency of the Republic of Indonesia (BAKAMLA RI), the Australian Border Force (ABF), Maritime Security